2022
DOI: 10.3390/foods11244030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Quality and Oxidative Stability of Hemp-Oil-Based Oleogels as an Animal Fat Substitute for Meat Patties

Abstract: The effect of the incorporation of rice bran wax (5%; 7%) or candelilla wax (3%; 7%) for production of hemp-oil-based oleogels was analyzed in this study. The experiment was carried out to replace between 0 and 100% of animal fat in meat patties with oleogels. Free fatty acids (FFAs), acid value (AV), oxidative stability index (OSI), conjugated diene value, malondialdehyde value, physicochemical properties, and the sensory properties of oleogels and meat patties were studied. The results indicated that hemp oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…A similar result was reported by Hamidioglu et al . (2022) for the rice bran and candelilla wax oleogels. The results explained that the stability of oleogel depends on the properties and fatty acid composition of the oleogelator used (Kupiec et al ., 2020; Hamidioglu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result was reported by Hamidioglu et al . (2022) for the rice bran and candelilla wax oleogels. The results explained that the stability of oleogel depends on the properties and fatty acid composition of the oleogelator used (Kupiec et al ., 2020; Hamidioglu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…(2022) for the rice bran and candelilla wax oleogels. The results explained that the stability of oleogel depends on the properties and fatty acid composition of the oleogelator used (Kupiec et al ., 2020; Hamidioglu et al ., 2022). Gedikoglu et al found that the utilisation of citrus fibre at either 3% or 5% levels in ground beef showed a pro‐oxidative influence (Hwang et al ., 2018); they proposed that the pro‐oxidant impact does not stem from hydrocarbons or wax esters.…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Hamidioglu et al. ( 2022 ), wax‐based oleogels were found to match the texture properties of pork fat, such as spreadability and adhesiveness, in meat patties. However, they also resulted in a decrease in juiciness and taste intensity when compared to meat patties containing 100% pork fat.…”
Section: Impact Of Oleogels On the Texture And Sensory Properties Of ...mentioning
confidence: 92%
“…These oleogels have been shown to reduce hardness, cohesiveness, gumminess, and chewiness values in products like sucuk (Yilmaz & Toksoz, 2022). In another study by Hamidioglu et al (2022), wax-based oleogels were found to match the texture properties of pork fat, such as spreadability and adhesiveness, in meat patties. However, they also resulted in a decrease in juiciness and taste intensity when compared to meat patties containing 100% pork fat.…”
Section: Meat Productsmentioning
confidence: 96%
“…It has been reported that some structural arrangements occur during oleogel formation due to the presence of self-assembled molecules, crystalline structures, or polymers through the physical modification of the oil entrapping the liquid oil and limiting its flowability [ 13 ]. Thus, recent studies demonstrated that food products with modified composition resulting from fat replacement by using different candelilla-wax-based oleogel formulations led to different improved technological parameters in various food models, including a chocolate butter substitute, meat, and bakery products [ 13 , 14 , 15 ]. Moreover, according to Cabrera et al [ 16 ], oils rich in unsaturated fatty acids result in stronger gels, which could provide more health benefits.…”
Section: Introductionmentioning
confidence: 99%